1991
DOI: 10.1159/000174860
|View full text |Cite
|
Sign up to set email alerts
|

Seminars in Thrombosis, Thrombolysis and Vascular Biology

Abstract: Platelets contribute to normal hemostasis by adhering to subendothelial tissues after vascular damage has taken place and then recruiting additional platelets through the process of aggregation. Activation of the coagulation cascade ultimately results in fibrin deposition. In pathological conditions, thrombogenic surfaces act as a nidus for platelet adherence and thrombus formation. The ability of platelet-inhibiting agents to prevent or impair platelet-mediated thrombotic and thromboembolic events is of vital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…The FBs are the main cells in the tunica adventitia. A large number of studies have demonstrated that vascular cells play a critical role in maintaining the normal functions of blood vessels . According to the basic principle of tissue engineering, vascular cells are the initial candidates for vascular regeneration.…”
Section: Terminally Differentiated Vascular Cellsmentioning
confidence: 99%
“…The FBs are the main cells in the tunica adventitia. A large number of studies have demonstrated that vascular cells play a critical role in maintaining the normal functions of blood vessels . According to the basic principle of tissue engineering, vascular cells are the initial candidates for vascular regeneration.…”
Section: Terminally Differentiated Vascular Cellsmentioning
confidence: 99%
“…Further, both experimental and clinical observations have demonstrated a major role of platelets in the pathophysiology of thrombotic states and vascular diseases (Becker 1991; Gori 2011; Kaliman et al 1983) and there is a link between platelet activation, arrhythmogenesis and sudden death (Flores 1996). Moreover, platelets are involved in the pathobiology of myocardial ischemia, infarction and hypertension (Fuster et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In our model, the pulmonary hypertension continued for 6-8 h. The reduction of PAP after pulmonary embolization occurred by focal vascular recanalization. Recently, it has become clear that the vas cular endothelium not only acts as a mechanical barrier but is also organ saving with a vital role in vasomotor and thromboresistance, and is influenced by vasoactive com pounds such as prostacyclin and endothelium-derived relaxing factor [10,11].…”
Section: Discussionmentioning
confidence: 99%